Upper Extremity Kinematic and Kinetic Comparison of Anterior Versus Posterior Walkers During Functional Activities in Children with Cerebral Palsy - (:unkn) unknown (My University, 2015)
Introduction: Investigating the differences in upper extremity (UE) joint biomechanics between anterior and posterior walkers has been explored in limited contexts, even though research has shown that prolonged use of walking aids can lead to UE joint weakening or musculoskeletal injuries. Recent studies have investigated some of these differences in children with spastic diplegic cerebral palsy (CP) during gait; however, no research has been conducted that compare these UE joint biomechanical differences during functional activities or activities of daily living (ADLs). The aim of this study is to use motion analysis to compare kinematic and kinetic differences between anterior and posterior walker use during representations of ADLs at the glenohumeral (GH) joint. Methods: Ten children ages 6-18 (mean age 13.27), 4 males and 6 females, were recruited to complete gait, reaching, and sit-to-stand/stand-to-sit tasks for kinematic analysis. One subject was chosen as a representative subject, and kinetic data was analyzed for gait and reaching tasks. Data was collected at Shriner’s Hospital for Children (Chicago, IL) in the Motion Analysis Laboratory using a specially designed walker that could be switched between anterior and posterior styles. Results: During gait, statistically significant differences were found in maximum flexion/extension angles at the dominant GH joint, with posterior walkers averaging greater minimum extension (-14.81 degrees +/- 20.83) compared to posterior walkers (-27.35 degrees +/- 13.60), as well as significant differences in the flexion/extension ROM in the dominant GH joint, with anterior walkers averaging 24.02 degrees +/- 15.95 versus 16..49 degrees +/- 8.26 for posterior walkers. During forward reaching, anterior walker usage resulted in an average reaching distance of 109.25mm +/- 76.65, which was statistically further than the 73.85mm +/-37.34 average seen during posterior walker usage. For sit-to-stand, anterior walker use resulted in an average of 4.82 seconds +/- 3.02, which was statistically faster than with a posterior walker (15.08 seconds +/-6.47). For stand-to-sit, posterior walker use resulted in an average of 5.89 seconds +/- 2.40, which was statistically faster than with an anterior walker (10.41 seconds +/-5.44). For kinetics during gait, the subject demonstrated a statistically significant increase in maximum anterior force (21.38 %BW +/- 3.54) and a greater maximum inferior force (-21.55 %BW +/- 2.65) for the dominant GH joint with an anterior walker versus a posterior walker. During forward reaching, peak anterior forces acting at the non-dominant GH joint (maximum 8.35 %BW +/- 0.21, minimum 5.68 %BW +/- 0.90) were significantly different between anterior and posterior walker usage. Also, a significantly different maximum medial force (-16.75 %BW +/- 1.85) was detected for posterior walkers. For moments, anterior walker usage resulted in a significantly greater minimum adduction moment (1.27 %BWxH +/- 0.04), and significantly greater peak internal rotation moments (maximum 1.56 %BWxH +/- 0.13, minimum 1.17 %BWxH +/- 0.03; Tables 8, 9; Figure 4). During lateral reaching, a significantly greater minimum medial force occurred at the non-dominant GH joint when using an anterior walker (11.29 %BW +/- 1.78). Anterior walker use resulted in significantly greater peak internal rotation moments (maximum 1.70 %BWxH +/- 0.37, minimum 1.51 %BWxH +/- 0.31), whereas posterior walker use led to a significantly greater maximum flexion moment (1.63 %BWxH +/- 0.12). Conclusion: Anterior and posterior walker use during gait and functional activities results in different kinematic and kinetic values in the GH joint, all of which should be considered during the walker prescription process.